Corporate Governance and Covenants Restrictiveness in Private Debt Contract - Abu Bakar, Intan Suryani; Mather, Paul; George, Tanewski (Contemporary Accounting Research, 2012)
Both corporate governance and covenants separately have been shown to play a role in mitigating agency problems associated with debt. Accordingly, we examine the association between corporate governance and the restrictiveness of covenants on a sample of newly syndicated loans in the U.S. private debt market. Cross-sectional results support the argument that, ceteris paribus, firms with stronger corporate governance are perceived by debtholders as less likely to engage in ex post opportunism, thereby reducing the need for particularly restrictive covenants. More specifically, the results indicate that both a corporate governance score and board independence are positively and significantly associated with covenant slack. While the results also show that independent directors’ financial expertise and covenant slack are positively related, there is no evidence to suggest that slack is associated with “busy” directors or CEO duality. Overall, the empirical evidence supports the hypothesis that debtholders perceive aspects of corporate governance to be beneficial and factor them into their contracting decisions.